2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319993
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency overactivation in dyslexia: Evidence from resting state Magnetoencephalography

Abstract: In this study, we compared the brain activation profiles obtained from resting state Magnetoencephalographic (MEG) activity in 15 dyslexic patients with the profiles of 15 normal controls, using power spectral density (PSD) analysis. We first estimated intracranial dipolar MEG sources on a dense grid on the cortical surface and then projected these sources on a standardized atlas with 68 regions of interest (ROIs). Averaging the PSD values of all sources in each ROI across all control subjects resulted in a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In the macaque, delta‐band phase has been observed to regulate theta‐band oscillatory amplitude while hearing tones (Lakatos et al ., ); in the rat, delta‐band phase was found to regulate stimulus‐dependent spiking rate under acoustic stimulation (Kayser et al ., ). A further source of evidence for the top‐down regulation of the theta band during speech processing comes, again, from the dyslexic population: at rest already, dyslexic subjects exhibit increased power and coherence of frontal delta‐band oscillations relative to controls (Arns et al ., ; Pagnotta et al ., ), predicting their behavioural deficits in speech processing (Arns et al ., ). In concert, during speech perception proper, dyslexic subjects exhibit reduced bottom‐up synchronisation of gamma‐ (Lehongre et al ., , ), theta‐ (Lehongre et al ., ) and delta‐band oscillations (Hämäläinen et al ., ; Molinaro et al ., ).…”
Section: Neural Oscillations In Speech Processingmentioning
confidence: 99%
“…In the macaque, delta‐band phase has been observed to regulate theta‐band oscillatory amplitude while hearing tones (Lakatos et al ., ); in the rat, delta‐band phase was found to regulate stimulus‐dependent spiking rate under acoustic stimulation (Kayser et al ., ). A further source of evidence for the top‐down regulation of the theta band during speech processing comes, again, from the dyslexic population: at rest already, dyslexic subjects exhibit increased power and coherence of frontal delta‐band oscillations relative to controls (Arns et al ., ; Pagnotta et al ., ), predicting their behavioural deficits in speech processing (Arns et al ., ). In concert, during speech perception proper, dyslexic subjects exhibit reduced bottom‐up synchronisation of gamma‐ (Lehongre et al ., , ), theta‐ (Lehongre et al ., ) and delta‐band oscillations (Hämäläinen et al ., ; Molinaro et al ., ).…”
Section: Neural Oscillations In Speech Processingmentioning
confidence: 99%
“…Increased bilateral, or reversed asymmetric patterns of activation for the theta range have been found in affected people compared to controls (Spironelli et al, 2008;Lizarazu et al 2015). Likewise, decreased theta range oscillations have been observed in dyslexics in non-synchronized background brain activity (Fraga González et al, 2016;De Vos et al, 2017; although see Babiloni et al, 2012;Pagnotta et al, 2015 for opposite findings). This latter finding might be indicative of an altered interaction between the auditory cortex and the background activity of the cortex (De Vos et al, 2017) and/or of atypical brain connectivity patterns (Fraga-González et al, 2016).…”
Section: Theta (~4-10 Hz)mentioning
confidence: 93%
“…These two ROIs were included because it has been shown that right homologues of left language areas are often recruited when dysfunction in the left hemisphere needs to be compensated. This can be seen in aphasia (Dominguez et al 2014 ; Vitali et al 2007 ), dyslexia (Pagnotta et al 2015 ; Sun et al 2010 ; Waldie et al 2013 ), age-associated cognitive decline (Meinzer et al 2009 , 2013 ), task difficulty (Gur et al 2000 ) and in response to perturbation via transient brain stimulation (Hartwigsen et al 2013 ). Connectivity analyses in the present study were conducted with partial correlations, a standard technique for analysing functional connectivity (Marrelec et al 2006 ; Ryali et al 2012 ; Sandberg 2017 ).…”
Section: Introductionmentioning
confidence: 99%